(untitled) - The American Assembly, Columbia University (Englewood Cliffs, N.J., 1984)
This volume in the distinguished American Assembly series addresses a timely question. What are our prospects for, and roadblocks to technological innovations.
Keywords: Đổi mới công nghệ,Technological innovations; Hội nghị,Congresses; Hoa Kỳ,United States